Transparency in Denmark's OpenAid.dk: A mixture of light and darkness - Ole Therkildsen (Danish Institute for International Studies (DIIS), 2019)
The general public has access to information about Danish aid on OpenAid.dk run by the Danish Ministry of Foreign Affairs. It builds on the International Aid Transparency Initiative (IATI), which aims at improving aid coordination, accountability and effectiveness. The central idea is that OpenAid.dk empowers citizens, politicians, journalists and civil society organisations themselves to extract information about the "what", "where", "when" and "which results" of Danish aid. The publication of Danida's Annual Reports is therefore deemed unnecessary. How useful is the database in answering such questions? (a) OpenAid.dk does throw light on a wealth of detailed financial information about bilateral Danish funding over time at the country level. However, it is not user-friendly; (b) it hardly provides any information about the performance and results of such activities; (c) the purposes and results of Denmark's support to multilateral organizations and to Danish ministries dealing with refugees are largely left in the dark. Denmark's aid transparency is mediocre, which international comparisons also show. As a result aid accountability and democratic debates on aid suffer. Improving public access to relevant, user-friendly and more transparent information about Danish aid and its results is clearly needed. Six proposals on this are presented in the working paper.
Keywords: 330